Theoretical analysis of orientations and tautomerization of genistein in β-cyclodextrin - Chonnikan Hanpaibool (2018)
© 2018 Genistein is an isoflavone with promising pharmaceutical applications. However, its low water solubility interferes with its potency, and therefore cyclodextrins (CDs) have been considered as possible drug delivery system (DDS). To investigate the complexation mechanism of genistein in cyclodextrin, we employed molecular dynamics (MD) simulations based on classical potentials and the density-functional tight-binding (DFTB) quantum chemical potential. Both classical and quantum chemical MD simulations predict that the phenol ring of genistein is preferentially complexed in the cavity of CD. The complexation process reduces the water-accessible solvation shell, and it is found that a hydrogen bond is formed between genistein and CD. The DFTB-based MD simulations reveal that spontaneous keto-enol tautomerization occurs even within a hundred picoseconds, which suggests that the encapsulated genistein is complexed in the ordinary enol form of the drug molecule. Analyses of the molecular charge distributions suggest that electrostatic interactions partially induce the complex formation, rather than extensive formation of hydrogen bonds.